Antiulcer Activity of Leaf Extracts of Pongamia pinnata Linn. - NAGARATHNA, P.K.M.; RAMESH, K.; PRABHAKAR, T.; GOPALAOVIRAO, M.; SHETTY, RAMACHANDRA (Asian Journal of Chemistry, 2010)
Preliminary phytopharmacological investigations of different extracts of leaves of Pongamia pinnata Linn. revealed the presence of flavonoids, strelos and saponins and showed promising antiulcer activity. The ethanol, petroleum ether and aqueous extracts of leaves of Pongamia pinnata Linn. were screened for their antiulcer activity at different lethal doses screened against several experimental models of ulcer in rats. The ethanol and petroleum ether extracts showed significant reduction in the pylorus and aspirin induced ulcers in rats. These results emphasize on the need to diversify in to alternative therapeutic approaches pertaining to herbal medicine wherein a single easily available plant may provide answers to several therapeutic challenges as observed in the antiulcer activity shown by different extracts of Pongamia pinnata Linn.